Developing a legal framework for negotiating development contributions through planning agreement for promoting sustainable development in West Malaysia - Siti Sarah binti Sulaiman (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
Malaysia is experiencing rapid economic development in both urban and rural areas and experiencing an unprecedented scale of growth especially land development and exploitation of natural resources. This increased number of development activities especially those involving infrastructure development has given rise to environmental degradation, sacrificing recreational areas, weakened hill slopes, depletion of natural resources, flash flood, landslide and climate change to list down some adverse problems. Despite the fact that development activities can cause adverse impact to the environment, these activities cannot be prevented completely. Principles of sustainable development were considered and embedded at all levels of decision-making process of the land use planning and development control system by the local planning authority. The local planning authority who is responsible for regulating and monitoring development is required to take into consideration the sustainable development criterions in the decision-making process to ensure the needs of the society is balanced. The local planning authority is empowered to impose conditions and restrictions on any application for planning permission to ensure the proposed development will be carried out in accordance with the specific regulations, guidelines and standards. However, the discretionary power to impose conditions and limitations are not absolute and they were caught by the decision in the case of Associated Provincial Pictures Houses Limited v Wednesbury Corporation [1948] 1 KB 223, where the court set out the limits of the powers of the local planning authority in imposing conditions. The court held that “conditions must be reasonable and related to the planning activities”. This decision has become a precedent for those seeking to challenge the decision conditions imposed on a grant of planning permission on the ground of unreasonableness. The local planning authority often imposes conditions requiring the developer to make contributions especially in providing public amenities including environmental protection measures. However, the local planning authority is often faced with challenges from applicants who refuse to fulfil the conditions imposed and agreed between them. This incident has prompted the local planning authority to resort to using private agreements to bind the project proponents to comply with the terms agreed and sealed in a documented agreement. This practice of negotiating development for making contributions between the local planning authority and the developers is informal in nature and not regulated by any particular law except the law of contract for redressing the breach of the agreement. This research using a combination of techniques including analysis of court cases and sample of agreements and interviews traced and confirmed the existence of the informal practice of negotiating development contributions and the use of planning agreement to seal the contract. The method used also differs from one local planning authority to the other especially in respect of the terminologies used, the manner of negotiation, implementation and enforcement of the provisions agreed between the parties to the planning agreement. A cursory review of the practice in England in the United Kingdom, New South Wales in Australia and New Zealand will be made to identify best practices for Malaysia. Thus, the objective of this research is to propose a legal framework to regulate the practice of negotiating development to gain developers contributions towards promoting sustainable development in West Malaysia.